PENGARUH KONSENTRASI PENDUDUK INDONESIA DI PULAU JAWA TERHADAP KESEJAHTERAAN MASYARAKAT - Asep Fikri Nur Arif; Nunung Nurwati (Jurnal Ilmu Kesejahteraan Sosial HUMANITAS, 2022)
The concentration of Indonesia's population on the island of Java, which reaches 56.10%, will gradually have many negative effects on the people themselves. Many factors cause the population of Java Island to be more than other islands. One of the main factors is the pull factor of Java Island which has better facilities compared to other regions. The unequal distribution of the population can reduce the level of welfare of the people in the region, such as increasing the number of unemployed people because there are fewer job opportunities than those looking for work to, then increasing the level of crime that has to be done to meet basic needs such as food. The approach through social justice theory is used this article provides explanations and solutions that are linear to the problems faced, options that can be made such as accelerating development outside Java, transmigration outside Java to tightening regulations in the demographic realm such as tightening the minimum age for marriage, family planning programs to reduce birth rates, and tightening the rules of immigration between islands can be an option to achieve justice and social equality for all Indonesians.